Why inositol supplementation may help to recover side effects induced by mood stabilizers and anticonvulsant drugs - Zdravko Kamenov; Elisa Lepore; Mario Montanino Oliva; Virginia Unfer; Vittorio Unfer (Nutrimentum et Curae)
Lithium, valproic acid and carbamazepine are the most used mood stabilizers and anticonvulsant drugs. They share the depletion of myo-inositol in the central nervous system as mechanism of action. However, such therapies may expose patients to several side effects that negatively influence their quality of life, leading to a poor compliance and a poor prognosis. Gathering scientific evidence explaining why myo-inositol supplementation may recover side effects without dampening the central therapeutic action of these drugs is the purpose of this review.